Las relaciones entre Latinoamérica e Irán durante la última década de la dinastía Pahleví - Camacho Padilla, Fernando (Jahrbuch für Geschichte Lateinamerikas, 2019)
During the 70s, Iran and several countries of Latin America consolidated their diplomatic relations. Most of the Latin American embassies opened their doors in Tehran those years, and likewise Iran established its representations in Venezuela and Mexico. The Shah had important personal connections with the presidents Carlos Andrés Pérez, with whom he engaged in developing cooperation projects, and Luis Echeverría, designing together commercial strategies within the framework of the Organization of the Petroleum Exporting Countries (OPEC). This article presents and analyzes some of the most significant episodes of this period, taking into consideration aspects such as the opening of Latin American embassies in Tehran, Iran foreign relations with Venezuela, Chile and Mexico, the Cuban support for the opposition groups, the Shah’s exile in Cuernavaca and Panama and, lastly, the effect of the 1979 revolution on the Iranian relations with these states.
Keywords: Cold War, Revolution, Islamic Republic, Shah, Exile, Cuba.